An Efficient Implementation of the Entire Transforms in the H.264/AVC Encoder using VHDL - Farhad Rad; Ali Broumandnia (International Journal of Reconfigurable and Embedded Systems (IJRES), 2013)
The H.264/AVC standard achieves remarkable higher compression performance than the previous MPEG and H.26X standards. One of the computationally intensive units in the MPEG and H.26X video coding families is the Discrete Cosine Transform (DCT). In this paper, we propose an efficient implementation of the DCT, inverse DCTs and the Hadamard transforms in the H.264/AVC encoder using VHDL. The synthesis results indicate that our implementation of the entire transforms achieves lower power, delay and area consumption compared to the existing architectures in the H.264/AVC encoder.